2021
DOI: 10.1097/shk.0000000000001726
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Porcine Study in Low Cardiac Output of Vasoactive and Inotropic Drug Effects on the Gastrointestinal Tract

Abstract: Background: Splanchnic vasodilation by inodilators is an argument for their use in critical cardiac dysfunction. To isolate peripheral vasoactivity from inotropy, such drugs were investigated, and contrasted to vasopressors, in a fixed low cardiac output (CO) model resembling acute cardiac dysfunction effects on the gastrointestinal tract. We hypothesized that inodilators would vasodilate and preserve the aerobic metabolism in the splanchnic circulation in low CO. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…First, high-dose of norepinephrine may induce oxidative stress and myocardial cells insult but also alter sepsis-associated immunomodulation ( 90 ). Furthermore, high-dose of norepinephrine may impair the splanchnic circulation with an increase in systemic and mesenteric vascular resistances ( 91 ). Nevertheless, a large randomized trial, the SEPSISPAM study, assessed the effects of two levels of mean arterial pressure in 776 patients with septic shock ( 92 ).…”
Section: Discussion and Review Of The Different Available Vasopressorsmentioning
confidence: 99%
“…First, high-dose of norepinephrine may induce oxidative stress and myocardial cells insult but also alter sepsis-associated immunomodulation ( 90 ). Furthermore, high-dose of norepinephrine may impair the splanchnic circulation with an increase in systemic and mesenteric vascular resistances ( 91 ). Nevertheless, a large randomized trial, the SEPSISPAM study, assessed the effects of two levels of mean arterial pressure in 776 patients with septic shock ( 92 ).…”
Section: Discussion and Review Of The Different Available Vasopressorsmentioning
confidence: 99%
“…[ 14 ] In particular, the use of high doses of norepinephrine is associated with more frequent atrial fibrillation, [ 14 ] possible induction of oxidative stress and insult to myocardial cells, [ 13 ] and possible alterations in the splanchnic circulation. [ 15 ] Second, the use of high doses of catecholamines, known as “vasopressor load,” is directly related to mortality in patients with septic shock regardless of the targeted mean arterial pressure (MAP), because of catecholamine-induced cardiac toxicity. [ 16 ] Third, norepinephrine (but not vasopressin) may alter sepsis-associated immunomodulation by dysregulating the immune response through anti-inflammatory effects, thus contributing to sepsis-induced immunoparalysis with persistent adrenergic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Potent vasodilators and constrictors have been used clinically to combat the cardiovascular and metabolic effects of low flow in this condition, to mixed affects. Seilitz et al (17) have developed a swine mode of cardiac dysfunction to test two inodilators (Levosimendan and milrinone) and two vasoconstrictors (vasopressin and norepinephrine) commonly used in this condition. The authors found that inodilators had negligible vasodilatory effects on the gastrointestinal circulation.…”
mentioning
confidence: 99%